2014
DOI: 10.1111/ijfs.12679
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oven temperature profile and different baking conditions on final cake quality

Abstract: This study discusses the effect of airflow on oven temperature profiles, the internal cake temperature and the final cake quality. It was found that the presence of airflow reduced the oscillation in the oven temperature profile from 12.98-30.27% to 3.17-4.02%. The bottom of the oven chamber experienced the greatest reduction in temperature oscillation in the presence of airflow. During the second stage of baking with airflow, the heating rate was increased from 5.07 to 7.52°C min À1 and 8.35°C min À1 to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The higher weight loss was owing to the higher loss in water. This finding also reinforced that the heating with airflow in the air fryer exhibits higher efficiency in heat supply [ 9 , 10 ], suggesting that a shorter heating duration should be adopted in its household application compared to the heating time setting of conventional ovens.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…The higher weight loss was owing to the higher loss in water. This finding also reinforced that the heating with airflow in the air fryer exhibits higher efficiency in heat supply [ 9 , 10 ], suggesting that a shorter heating duration should be adopted in its household application compared to the heating time setting of conventional ovens.…”
Section: Resultssupporting
confidence: 57%
“…As shown in Figure 1 A, the air fryer caused irregular bumps on the surface of the cupcakes. The volume expansion of the cupcakes during air frying creates a more porous structure with larger voids [ 9 ]; therefore, the highly porous microstructure might differentiate in appearance between the ground air-fried cupcake samples and the oven-baked samples. The lower uniformity of the air-fried cupcakes might be due to the presence of the forced hot airflow during heating because a higher volume expansion could be observed when the heat penetrated the cupcakes [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature is the main influencing baking parameter for quality. Shahapuzi et al [22] studied the effect of airflow on oven temperature profile and reported an increase of 5-10% in cake volume expansion rate when airflow condition was applied. In order to compare the numerical and experimental airflow pattern within the baking chamber, the entire baking area was sectioned into three zones vertically (each of 0.234 m wide and 0.64 m high).…”
Section: Scheffler Reflector and Receivermentioning
confidence: 99%
“…The results showed that breads baked with infrared had higher moisture content, higher volume, lower crumb firmness and similar overall quality score compared with conventional baking process. Shahapuzi et al (2015) analysed the effect of the airflow on the oven temperature profile, the internal cake temperature and the cake quality. The authors found that the presence of airflow induced a faster heating rate, a higher volume expansion rate and a more porous crumb texture.…”
Section: Introductionmentioning
confidence: 99%